V0.5Nb0.5ZrTi refractory high-entropy alloy fabricated by laser addictive manufacturing using elemental powders. (June 2023) - Zhu, Peng; Yu, Yao; Zhang, Cheng; Zhou, Qingjun; An, Bailing; Guo, Rong; Chan, K.C.; Liu, Lin
Abstract: In this work, a V0.5 Nb0.5 ZrTi refractory high-entropy alloy is successfully fabricated by the selective laser melting (SLM) method using elemental powders as precursors. A crack-free SLM-prepared (SLMed) sample with a nearly single BCC structure is acquired with a volume energy density (VED) of 333 J/mm 3 . However, when the VED is lower or higher than 333 J/mm 3, microcracks are generated in the SLMed samples. The finite element method simulation reveals that there are two mechanisms for generation of cracks. When VED < 333 J/mm 3, Zr particles are not completely melted. Cracks are formed around the Zr particles due to the crystalline structure and coefficient of thermal expansion mismatches between the unmelted Zr particles and the alloyed BCC matrix. When VED > 333 J/mm 3, cracks are formed due to thermal stress induced by the large temperature gradient during the SLM process. In addition, the SLMed crack-free sample exhibits much better mechanical properties than the as-cast counterpart. The current study provides a reference for the application of SLM technology to prepare refractory high-entropy alloys with excellent mechanical properties using elemental powders as the precursor. Highlights: Technology control effectively suppressed the cracks in the V0.5 Nb0.5 ZrTi refractory high-entropy alloy during SLM process. Two different mechanisms of crack generation in the V0.5 Nb0.5 ZrTi refractory high-entropy alloy were investigated. The microstructure and mechanical properties of the V0.5 Nb0.5 ZrTi refractory high-entropy alloy were studied.